2016
DOI: 10.1111/mec.13800
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA reveals differences in behaviour and sociality between brown bears and extinct cave bears

Abstract: Ancient DNA studies have revolutionized the study of extinct species and populations, providing insights on phylogeny, phylogeography, admixture and demographic history. However, inferences on behaviour and sociality have been far less frequent. Here, we investigate the complete mitochondrial genomes of extinct Late Pleistocene cave bears and middle Holocene brown bears that each inhabited multiple geographically proximate caves in northern Spain. In cave bears, we find that, although most caves were occupied … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 48 publications
5
64
0
Order By: Relevance
“…; Fortes et al. ), we can assume that different versions of the structures of P4 and M2 are fixed in different populations. Against this background, the diversity of M1 becomes more noticeable and in several cases comparable with premolar and second molar diversity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…; Fortes et al. ), we can assume that different versions of the structures of P4 and M2 are fixed in different populations. Against this background, the diversity of M1 becomes more noticeable and in several cases comparable with premolar and second molar diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Another indirect confirmation of differences in the genetic and epigenetic regulation of the teeth parameters is associated with an increase in relative orderliness for P4 and M2 at the population level. Reasoning by analogy and taking into account the relatively sedentary life style of cave bears ( Abelov a 2006;Frischauf et al 2015;Fortes et al 2016), we can assume that different versions of the structures of P4 and M2 are fixed in different populations. Against this background, the diversity of M1 becomes more noticeable and in several cases comparable with premolar and second molar diversity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outermost layer of long bones is usually removed prior to sampling for ancient DNA in an effort to remove modern DNA contamination (Damgaard et al., ; Fortes et al., ; Hansen et al., ; Rohland & Hofreiter, ). While this idea is intuitively plausible and observed in the majority of samples analysed here, we found that for some bones, this is not the case.…”
Section: Discussionmentioning
confidence: 99%